Excitons and trions in spherical semiconductor quantum dots - Kupchak, I.M.; Kryuchenko, Yu.V.; Korbutyak, D.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
An original iterative procedure has been developed to obtain energy spectrum of neutral and charged excitons (positive and negative trions) in spherical semiconductor quantum dots (QD) imbedded into a dielectric material. Numerical calculations are made using the effective mass approximation and Hartree-Fock method. A combined effect of heterointerface polarization (image force potential) and finite band-off-sets on the energy spectrum of excitons and trions in QDs is considered for the first time. It is shown that binding energies of excitons and trions in such QDs can be substantially larger than those in bulk semiconductors due to spatial and “dielectric” confinement effects.